ANALISIS FAKTOR PEMILIHAN KOS-KOSAN MENGGUNAKAN KMO - BARTLETT’S TEST DAN KAITANNYA PADA KEINGINAN MENDIRIKAN USAHA - RB, Linda Desafitri (Jurnal Pengabdian dan Kewirausahaan, 2018)
Population growth in Indonesia especially in Jakarta can be seen as an opportunity for residential business establishment called boarding houses. The need for boarding house become one of the important things for residents in Indonesia, especially around the office and campus. The distribution of the population in search of employment and lecture forces the situation for the need of boarding house given the relatively short residence time or the relatively close location. This study aims to analyze the dominant factors that become the consideration of residents in choosing the boarding houses in Jakarta. Factors used in this research are facilities, price, location, security, boarding house environment, reputation, and reference. The study involved 34 boarding house residents in Jakarta. The analysis uses KMO-Bartlett test to analyze priority factors. The results of this study explain that the existence of public facilities for example: waiting room guests, TV watching room together, shared pantry, public toilets/bathrooms and places/buildings are well maintained boarding house be a major factor in consideration of residents. The next factors that become the main consideration is to choose a boarding house due to friend factor and reputation/image place/owner boarding house. Suggestion of this research is more emphasize on effort to make boarding house business in Jakarta where can consider to provide public facilities such as a comfortable waiting room that allows for space to communicate between residents and guests and also among co-inhabitants boarding house. Other factors such as making a small garden or providing crops are important to make the atmosphere of boarding house cooler and soothing. Routine maintenance such as wall painting and cleaning floors boarding house corridors need to be done so that residents boarding house feel more comfortable. Keywords: boarding house, price, amenities, environment